Linking System of Care Services to Flourishing in School-Aged Children with Autism - Wanqing Zhang; Stephanie Reszka (Disabilities)
Flourishing in children is an indicator of positive development in the areas of emotional, social, and cognitive development. Using a recent dataset from the US National Survey of Children’s Health, this study investigates the association between access to a quality healthcare system and flourishing indicators in school-aged children with autism. The outcome variable describes the proportion of children aged 6–17 with autism meeting the flourishing criteria, which include measures related to learning, resilience, and self-regulation. The main independent variable includes six core indicators for school-aged children and adolescents, which assess whether the family feels like a partner in their child’s care, the child has a medical home, receives regular medical and dental preventive care, has adequate insurance, has no unmet needs or barriers to accessing services, and has prepared for transition to adult healthcare. Multivariable logistic regression models were used to examine the relationships between various independent variables and the outcome of interest. The results show that children with autism who receive comprehensive and coordinated care are more likely to flourish compared to those without such care for five of these six indicators, while controlling for sex, race, parental education, household income, self-reported autism severity, general health status, and the number of adverse childhood experiences. Children with autism are more likely to flourish when their families and healthcare providers work together effectively. Addressing gaps in the quality care system is essential for developing holistic approaches that empower children with autism to thrive and reach their full potential. Supportive health policies and effective coordination between families and healthcare providers are crucial for fostering the flourishing of children with autism, ensuring comprehensive, individualized, and continuous care.